The potential role of short chain fatty acids improving ex vivo T and CAR-T cell fitness and expansion for cancer immunotherapies - González-Brito, Adrián; Uribe-Herranz, Mireia (Frontiers in Immunology, 2023)
Adoptive cell therapies, like tumor-infiltrating lymphocytes or chimeric antigen receptor T cells, have become an important immunotherapeutic approach against cancer. One of the main struggles of T cell immunotherapies is how to obtain the most effective T cell phenotype, persistence, and differentiation potential to infuse into patients. Adjusting the T cell ex vivo cell culture conditions is a key factor to increase and improve the efficacy of cellular immunotherapies. In this review, we have summarized the ex vivo impact of short chain fatty acids, a group of gut microbiota derived metabolites, on T cell culture and expansion for immunotherapies. There is a complex gut microbiota-immune system interaction that can affect antitumor immunotherapy efficacy. Indeed, gut microbiota derived metabolites can modulate different biological functions in the immune system local and systemically.